Update on the multi-layered levels of zinc-mediated immune regulation. (July 2021) - Wessels, Inga; Fischer, Henrike J.; Rink, Lothar
Abstract: The significance of zinc for an efficient immune response is well accepted. During zinc deficiency, an increase in the myeloid to lymphoid immune cells ratio was observed. This results in a disturbed balance of pro- and anti-inflammatory processes as well as defects in tolerance during infections. Consequently, instead of efficiently defending the body against invading pathogens, damage of host cells is frequently observed. This explains the increased susceptibility to infections and their severe progression observed for zinc deficient individuals as well as the association of autoimmune diseases with low serum zinc levels. Together with the advances in techniques for investigating cellular development, communication and intracellular metabolism, our understanding of the mechanisms underlying the benefits of zinc for human health and the detriments of zinc deficiency has much improved. As analyses of the zinc status and effects of zinc supplementation were more frequently included into clinical studies, our knowledge of the association of zinc deficiency to a variety of diseases was strongly improved. Still there are several areas in zinc biology that require further in-depth investigation such as the interaction with other nutritional elements, the direct association between zinc transportation, membrane-structure, receptors, and signaling as well as its role in cell degeneration. This article will describe our current understanding of the role of zinc during the immune response focusing on the most recent findings and underlying mechanisms. Research questions that need to be addressed in the future will be discussed as well. Graphical Abstract: ga1 Highlights: Activation-induced zinc signals play a functional role in immune cells. Zinc is decisive during the polarization of Treg, TH 17 and TH 9 cells. Zip7 and Zip10 play major roles during B cell activation. Growth-factor-induced signalling in neutrophils is largely altered by zinc. Polarization and the inflammatory response of macrophages are governed by zinc.